The Family Wellness Program: a bench to bedside translation of behavioral and social science research into a clinical program for intimate partners of warfighters following traumatic brain injury - Brickell, Tracey A.; Wright, Megan M.; Baschenis, Samantha M.; Lange, Rael T.; Sullivan, Jamie K.; French, Louis M. (Frontiers in Health Services, 2025)
This report details a bench to bedside translation of behavioral and social science research into a clinical program as a result of a collaboration between two United States Defense Health Agency Centers of Excellence for warfighter traumatic brain injury (TBI) and brain health. Identifying a gap in health-related quality of life (HRQOL) measures, our team instigated a 7-year multisite effort to validate and develop generic and caregiver specific HRQOL domains for family members of warfighters and civilians with a TBI using state-of-the-science measurement development standards; the Traumatic Brain Injury Caregiver Quality of Life (TBI-CareQOL) measurement system. The TBI-CareQOL was integrated into the Defense and Veterans Brain Injury Center-Traumatic Brain Injury Center of Excellence 15-Year Longitudinal TBI Study designed to address four elements in a Congressional mandate (NDAA FY2007 Sec721 Public Law 109-364). Based on findings from the 15-Year Longitudinal TBI study and larger body of related literature demonstrating the bidirectional associations between warfighter neurobehavioral outcomes and family distress, relevant TBI-CareQOL measures were integrated into the Family Wellness Program (FWP) for intimate partner (IP) beneficiaries of warfighters with TBI in treatment for chronic neurobehavioral symptoms across the Defense Intrepid Network for Traumatic Brain Injury and Brain Health (DIN). The FWP screens IPs for clinically elevated HRQOL symptoms with clinical follow up offered in alignment with operations at each DIN treatment center and military base. In July 2024, the FWP was launched at the National Intrepid Center of Excellence at Walter Reed National Military Medical Center, and is currently expanding across the DIN.